Enhancement of the aroma in low-alcohol apple-blended pear wine mixed fermented with Saccharomyces cerevisiae and non-Saccharomyces yeasts. (1st February 2022) - Yang, Xueshan; Zhao, Fangqin; Yang, Liu; Li, June; Zhu, Xia
Abstract: Zaosu pear has a high yield and is widely planted in Northwest China. Recently, a large number of ripe fruits are spoiled in the orchards due to poor market. This cultivar has the potential to produce perry, so a novel fermentation strategy for Zaosu pear wine has been explored to reduce these huge losses. The mixed inoculation of M. pulcherrima 346 and S. cerevisiae ES488 allowed higher concentrations of aromatic esters and alcohols in pear wine than that involving pure S. cerevisiae culture. When Zaosu pear juice and apple juice were blended in a 60:40 ratio, the total content of aroma compounds increased by 18% compared with that in pure pear wine due to the increase in the ethyl esters, higher alcohols and terpenoids concentration. The optimum mixed fermentation parameters obtained using a single-factor test coupled with a Box–Behnken design were an initial pH of 3.7, 1.5:1 inoculation ratio of M. pulcherrima 346 and S. cerevisiae ES488, sequential inoculation time 45 h and making temperature 18 °C. The optimized wine sample was characterized by floral and fruity aromas, and more complex and rounded flavors. Overall, our study provides support for aroma enhancement of pear-apple wines. Highlights: Pear wine was mix fermented with different S. cerevisiae and non- S. cerevisiae strains . Adding apple juice increased the total concentration of esters and terpenoids in pear wine. Initial pH and inoculation time impact the sensory profile of pear-apple wines. Optimized fermentation parameters increase the concentration of esters with pear-like aroma. The aroma enhancing fermentation strategy helps to improve the pear-apple wine quality.